Next Generation Project Management In The Platinum Industry - H. W. Read (The Southern African Institute of Mining and Metallurgy, 2006)
The South African platinum industry finds itself in the midst of a rapidly evolving society that is no longer characterized by the apparent stability of the previous decades. The features of this society include increasing global competition, rapid technological innovation, a declining skills pool, major political transformation, a more challenging working environment as the mines reach deeper into the earth?s crust and a greater concern for human welfare. It is therefore axiomatic that new ways will have to be found to engage the all-pervasive change in the mining environment. Although in general terms project management is a universal endeavour for managing change, it takes place in a specific socio-techno-economic environment and geographical setting that gives it a particular context. The argument of this paper explores, analyses and synthesizes the impact of these changes on the emerging project management methodology. In essence, the management of change will inevitably contribute to the emergence of new dilemmas, issues and challenges. The change management process and procedures will also be affected by this change and in response, drive internal change of its own structures and organization. And, therefore, a new paradigm of project management will become apparent. A new project management model will then be proposed to the industry.